2014
DOI: 10.1080/14786419.2013.877902
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and orofacial anti-nociceptive activities of the stem bark aqueous extract ofAnadenanthera colubrina(Velloso) Brenan (Fabaceae)

Abstract: The anti-nociceptive and antioxidant activities of the Anadenantheracolubrina stem bark aqueous extract (AEAC) were investigated. AEAC (30 μg/mL) reduced 94.8% of 2,2-diphenyl-1-picrylhydrazyl radical and prevented 64% (200 μg/mL) of lipid peroxidation caused by 2,2'-azobis(2-methylpropionamidine) dihydrochloride-induced peroxyl radicals. AEAC treatment (200 and 400 mg/kg) significantly (p < 0.001) reduced mice orofacial nociception in the first (61.4% and 62.6%, respectively) and second (48.9% and 61.9%, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 8 publications
0
8
0
2
Order By: Relevance
“…However, the survey also highlighted the A. cearensis species used to treat respiratory diseases. Antimicrobial and antiproliferative [93] and antinociceptive and antioxidant activities [94] have been reported for the species A. colubrina ; however, no study was carried out to verify the activity of this species on the respiratory system was observed, whereas for the species A. cearensis in the study by Leal et al (2000) the bronchodilator potential of this species was demonstrated, thus confirming its efficacy for diseases affecting the respiratory (expectorant) system [95]. …”
Section: Resultsmentioning
confidence: 99%
“…However, the survey also highlighted the A. cearensis species used to treat respiratory diseases. Antimicrobial and antiproliferative [93] and antinociceptive and antioxidant activities [94] have been reported for the species A. colubrina ; however, no study was carried out to verify the activity of this species on the respiratory system was observed, whereas for the species A. cearensis in the study by Leal et al (2000) the bronchodilator potential of this species was demonstrated, thus confirming its efficacy for diseases affecting the respiratory (expectorant) system [95]. …”
Section: Resultsmentioning
confidence: 99%
“…The presence of bufotenine suggests that seeds from Anadenanthera were carried in the fox-snout pouch and may have been related to the archaeological plant. Within a South American context, bufotenine has been most widely documented in the seeds of Anadenanthera, while the stem/bark of the plant has not yielded evidence of bufotenine content (instead having trace amounts of DMT-oxide) (48). It is possible that the bufotenine is endogenously present in the unknown archaeological plant sample and that further morphological work will be needed to identify this plant stem.…”
Section: Discussionmentioning
confidence: 99%
“…A. colubrina stands out due its medicinal properties, which include the application for treatment of inflammatory disorders in different tissues [13,14]. Several studies have shown the various pharmacological properties of products derived from A. colubrina (mostly extracts and fractions from the leaves and roots) that include antimicrobial [12,15,16], antioxidant [17][18][19][20], wound-healing [21,22], anti-inflammatory [23], antinociceptive [24], and antiproliferative properties [18,25]. Despite the therapeutic potential, little information is available regarding the chemical properties and biological activities of the biopolymer extracted from the trunk exudate of A. colubrina, the red angico gum (RAG), of northeast Brazil.…”
Section: Introductionmentioning
confidence: 99%